Upper paleocene-lowermost eocene planktonic foraminiferal biostratigraphy and record of the paleocene-eocene thermal maximum in the Haymana Basin (Ankara, Turkey) - Tanık, Gamze (Middle East Technical University, 2017)
A rapid global warming event, called the Paleocene-Eocene Thermal Maximum (PETM), took place ca. 56 Ma, marking the Paleocene/Eocene boundary. This event is recorded by a turnover of planktonic foraminifera in deep marine settings, with occurrence of three species so-called planktonic foraminifera excursion taxa (PFET). This work was carried out in order to determine the record of this event in the Haymana Basin, Central Anatolia. The Haymana Basin provides a continuous sedimentary succession starting with Upper Cretaceous up to middle Eocene, where upper Paleocene-lower Eocene succession is represented by a deep marine shale succession, known as the Eskipolatlı Formation. A 33 meter thick stratigraphic section was measured from this formation, and 41 samples were taken. The samples were prepared by standard washing method, and planktonic foraminifera were picked from >63 and >106 μm fractions, and analyzed. Planktonic foraminifera were studied for biostratigraphic framework, 40 species belonging to 11 genera were identified, and 4 biozones were distinguished spanning through the late Thanetian and earliest Ypresian. In ascending order these biozones are as follows: Globanomalina pseudomenardii Zone, Morozovella subbotinae Zone, Acarinina sibaiyaensis Zone, and Pseudohastigerina wilcoxensis Zone. A quantitative study was conducted on 26 of the samples in order to establish the generic relative abundance changes throughout the measured section. As is in similar latitudes, the section withholds a dominance of Acarinina, accompanied by Subbotina and Morozovella genera. A smaller fraction of the assemblage is represented by Globanomalinids and Igorinids. A reworking/transportation problem is identified in the samples, causing difficulties determining the zonal boundaries. This situation, along with the quantitative results, can be interpreted to be related to the phases of turbiditic activity. With this study one representative of PFET, hence the chronostratigraphically short A. sibaiyaensis Zone was detected ...